John Wesley's Forty- Four Sermons: First Series - John Wesley 1703-1791; Edward Holdsworth Sugden 1854-1935 (UK Epworth Press, 1980)
consisting of forty-four discourses, published in four volumes, in 1746, 1748, 1750, and 1760 (fourth edition, 1787) to which are added nine additional sermons published in vols. I to IV of Wesley's collected works, 1771
edited and annotated by Edward H. Sugden
Sermons on several occasions . John Wesley's Standard Sermons . Reprint. Originally published: Standard sermons. 4th annotated ed. London : Epworth Press, 1955-1956.
Keywords: Spiritual Theology (3GddGghJ GdQhMjs; Theology -- Sermons; Methodist Church; Sermons, English -- 18th century